Ambulance Operational Services Information System At The Jakarta Department Of Health - Sri Rahayu; Desti Nanda Pramesti; Dira Aulia Aditya (CCIT Journal, 2022)
Information regarding monitoring of operational expenditures of the Regional Public Service Agency at the Emergency Ambulance Service Unit of the DKI Jakarta Health Office. Because the finances issued or used must be accurately informed. In this case, monitoring the operational expenses of the Regional Public Service Agency at the Emergency Ambulance Service Unit of the DKI Jakarta Health Service still has many obstacles. Constraints faced are such as the technical executor. The activity of submitting an accountability letter still has a long stage, the Verifier is not there so that the process of checking the accountability letter stops, the input of reports is carried out one by one by the Spending Treasurer using Microsoft Excel. The process of monitoring the operational expenses of the Regional Public Service Agency at the Emergency Ambulance Service Unit of the DKI Jakarta Health Office takes a long time. And another obstacle is the occurrence of classifying the type of operational expenditure. In this data analysis method, using Balanced Scorecard (BSC) analysis, system design uses Visual Paradigm to create UML (Unified Modeling Language), PHP programming language, MySQL to create databases. The result of this research is that an information system for monitoring operational expenditures of the Regional Public Service Agency can create and submit a letter of accountability and verification letters are carried out computerized, the Expenditure Treasurer no longer enters the general cash books one by one, the Expenditure Treasurer no longer classifies the types of operational expenditure in recap operational expenditure.